2012
DOI: 10.7863/jum.2012.31.12.2001
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Dispersion Ultrasound Vibrometry Based on a Different Mechanical Model for Soft Tissue Characterization

Abstract: he study of shear moduli has great potential for tissue characterization because the range of variation in the shear moduli is several orders more than that for the bulk moduli for various biological tissues. 1 An effective approach for noninvasively measuring the shear moduli is to quantify responses of the tissue stressed by external force. Three of the main challenges in obtaining the shear moduli of soft tissue are as follows: (1) remotely generating a shear wave with the frequencies of interest in a tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…For the Voigt model, the elasticity E is a constant in the frequency domain. As the Zener model describes creep and relaxation, while the Voigt model describes creep, the Zener model is equal to the Voigt model if (6) F1 (5) F2 (9) F3 (5) F4 ( Data are expressed as mean±standard deviation (SD) its elasticity E 2 is infinite (Chen et al, 2012 Our results are in agreement with the studies reported in the past. Asbach et al (2008) studied eight healthy volunteers and eight patients with biopsyproven liver fibrosis (grades 3-4) by magnetic resonance (MR) elastography.…”
Section: Discussionsupporting
confidence: 83%
“…For the Voigt model, the elasticity E is a constant in the frequency domain. As the Zener model describes creep and relaxation, while the Voigt model describes creep, the Zener model is equal to the Voigt model if (6) F1 (5) F2 (9) F3 (5) F4 ( Data are expressed as mean±standard deviation (SD) its elasticity E 2 is infinite (Chen et al, 2012 Our results are in agreement with the studies reported in the past. Asbach et al (2008) studied eight healthy volunteers and eight patients with biopsyproven liver fibrosis (grades 3-4) by magnetic resonance (MR) elastography.…”
Section: Discussionsupporting
confidence: 83%
“…6(c) where the estimated values of G = 1.7 kPa and η = 0.83 Pa·s are consistent with the values reported in previous studies [38]. However, in biological tissues, it is widely acknowledged that the inherent biological variability and the tissue preparation and storage methods can have a significant influence on the measured viscoelastic properties [45].…”
Section: Dispersion Curvessupporting
confidence: 88%
“…This is substantially lower than the reported SWV of 1.2 m/s using ARFI or FibroScan techniques with an external ultrasound pulsar . However, SWV depends on the frequency of the shear wave and declines substantially at pushing pulse frequencies below 200 Hz . ARFI and SDUV techniques use extremely short ultrasound pulses at frequencies in the KHz and MHz range and duration, whereas FibroScan uses a 50‐Hz pulser.…”
Section: Discussionmentioning
confidence: 67%